From Normal to Viral Body: Death Rituals During Ordinary and Extraordinary Covidian Times in Pakistan - Ali, Inayat (Frontiers in Sociology, 2021)
Death is far from being simply a physiologic event; it is a complex phenomenon with socio-cultural and politico-economic aspects. During extraordinary times such as the 2020 coronavirus pandemic, death becomes a contested site. I argue that the Pakistani government’s dealings with the bodies of people who die from COVID-19 have shifted the meaning of a normal dead body to a viral body that poses particular challenges to cultures and people, including the government. This article is both autoethnographic and ethnographic. It concurrently draws on my observations and participation in death rituals in a Pakistani village in Sindh province as a member of that society, and on a recent experience that I faced after the death of a gentle lady of my acquaintance due to COVID-19. I also build on my previous long-term ethnographic research in Pakistan and my ongoing research on COVID-19 in that country. I discuss the death rituals and ceremonies performed (1) during “ordinary” situations as background information; and (2) the changes in these rituals that have resulted from the coronavirus pandemic. My data demonstrate significant differences between usual and customary death rituals and those performed during Covidian times by government mandate, which have severely and negatively affected people’s mental health. I show the government’s “symbolic ownership” of the viral body, in that the government can control how people deal with their viral dead.